Сегментація методом керованого вододілув обробці зображень - Ткаченко, Д. А. (ХНУРЕ, 2019)
Quite often, when analyzing images, the problem of image segmentation arises. The most famous are two types of segmentation - segmentation by brightness for binary images and segmentation by color coordinates for color images. Segmentation methods can be viewed as a formalization of the notion of an object being distinguished from the background or concepts associated with a brightness gradient. Segmentation algorithms are characterized by some parameters of reliability and reliability of processing. They depend on how fully the additional characteristics of the brightness distribution in the areas of objects or the background, the number of differences in brightness, the shape of objects are taken into account.